Performance of An Airlift Membrane Bioreactor Under Different Aeration Rates - Kazemzadeh-Afshar, Mahsa; Sarrafzadeh, Mohammad Hossein; Mehrnia, Mohammad-Reza (Journal of Membrane and Separation Technology, 2012)
The treatment of a synthetic oily wastewater in an airlift submerged membrane bioreactor (AMBR) has been studied. A flat sheet Kubota membrane has been used for this purpose in the reactor with a working volume of 19 L. The volumetric oxygen transfer coefficient, oxygen uptake rate, treatment efficiency and fouling intensity were investigated for various aeration rates (0.2, 0.5, 0.7 and 1 m3/h). Based on the results, a COD removal efficiency of more than 93% - even for the lowest aeration rate – is reported. However, increasing the aeration rate resulted in higher kLa and higher microbial activity. The high aeration intensity resulted in breakage of activated sludge flocs and hence reduction in mean flocs size and release of extracellular polymeric substances (EPS). At an aeration intensity as high as 1m3/h, the maximum irreversible fouling was observed which is due to higher concentration of EPS and colloids that are the major foulants. Although the aeration may scour the membrane surface and avoid the formation of cake layer, it could induce more pore blocking fouling. In the studied range, the 0.7 m3/h is found to be the optimum aeration rate and the alteration of the aeration rate deteriorated the AMBR’s performance.